Mechanisms and Optimization Strategies of Paracrine Exosomes from Mesenchymal Stem Cells in Ischemic Heart Disease - Xiaorong Yin; Lizhi Lin; Fang Fang; Bin Zhang; Cheng Shen (Stem Cells International)
The morbidity and mortality of myocardial infarction (MI) are increasing worldwide. Mesenchymal stem cells (MSCs) are multipotent stem cells with self-renewal and differentiation capabilities that are essential in tissue healing and regenerative medicine. However, the low implantation and survival rates of transplanted cells hinder the widespread clinical use of stem cells. Exosomes are naturally occurring nanovesicles that are secreted by cells and promote the repair of cardiac function by transporting noncoding RNA and protein. In recent years, MSC-derived exosomes have been promising cell-free treatment tools for improving cardiac function and reversing cardiac remodeling. This review describes the biological properties and therapeutic potential of exosomes and summarizes some engineering approaches for exosomes optimization to enhance the targeting and therapeutic efficacy of exosomes in MI.